Marine Geology and Oceanography of the Pacific Manganese Nodule Province 1979
DOI: 10.1007/978-1-4684-3518-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Minerals, Metal Contents, and Mechanism of Formation of Manganese Nodules from the Central Pacific Basin (GH76-1 and GH77-1 Areas)

Abstract: Mineralogy, chemistry and microstructure of deep sea manganese nodules from the Central Pacific Basin have been studied by means of X-ray diffraction analysis, microspopy and electron microprobe analysis. The manganese nodules are composed of microscopically laminated phases of loA manganite and 8-Mn02. The 10~ manganite phase is a monominera1ic phase of crystalline manganese oxide with minor elements such as nickel and copper, and the 8-Mn02 phase is a submicroscopic mixture of colloidal particles of 2 line-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…Birnessite-Na4Mn14027*H20, according to Fleischer (1980)-apparently has somewhat similar properties (Burns and Burns, 1977). It is the nodules rich in todorokite and birnessite that are rich in nickel and copper and the other minor metals previously described as most abundant in the 5: 1-percent combined nickel and copper type (Burns and Fuerstenau, 1966;Barnes, 1967;Cronan and Tooms, 1969;Tooms and others, 1969;Margolis and Burns, 1976;Piper and Williamson, 1977;Calvert and Price, 1977;Halbach and Ozkara, 1979;Usui, 1979;Piper and others, 1979;Cronan, 1980;Bischoff and others, 1981). It is also the todorokite-rich nodules that have a manganeseiron ratio of >1.5 (Margolis and Burns, 1976;Piper and Williamson, 1977;Calvert and Price, 1977;Halbach and Ozkara, 1979).…”
Section: °Smentioning
confidence: 97%
See 4 more Smart Citations
“…Birnessite-Na4Mn14027*H20, according to Fleischer (1980)-apparently has somewhat similar properties (Burns and Burns, 1977). It is the nodules rich in todorokite and birnessite that are rich in nickel and copper and the other minor metals previously described as most abundant in the 5: 1-percent combined nickel and copper type (Burns and Fuerstenau, 1966;Barnes, 1967;Cronan and Tooms, 1969;Tooms and others, 1969;Margolis and Burns, 1976;Piper and Williamson, 1977;Calvert and Price, 1977;Halbach and Ozkara, 1979;Usui, 1979;Piper and others, 1979;Cronan, 1980;Bischoff and others, 1981). It is also the todorokite-rich nodules that have a manganeseiron ratio of >1.5 (Margolis and Burns, 1976;Piper and Williamson, 1977;Calvert and Price, 1977;Halbach and Ozkara, 1979).…”
Section: °Smentioning
confidence: 97%
“…Separate analyses of tops and bottoms showed that the tops are high in iron, cobalt, and lead and low in copper, nickel, molybdenum, zinc, and manganese and that the reverse is true for the bottoms. Calvert and Price (1977), Halbach and Fellerer (1980), Piper and others (1979), and Usui (1979) have suggested that the upper surfaces of such nodules (shown to be composed of vernadite) represent precipitate derived directly from seawater and that the bottoms (todorokite) represent a diagenetic precipitate by leaching of the underlying sediment. Concentrations of manganese, copper, nickel, cobalt, and zinc in the interstitial water of deep-sea sediments have been found to be higher than those in deep seawater, and Lynn and Bonatti (1965) and others (Bender, 1971;Renard and others, 1976) proposed that Mn*4 in the sediments is reduced to Mn*2 under low Eh conditions (perhaps created in part by the oxidation of buried organic matter, as Price and Calvert (1970) suggested), dissolved, carried upward, and precipitated under the oxidizing conditions prevailing at or near the surface.…”
Section: Effects Of Direct Precipitation From Seawater In Comparison mentioning
confidence: 99%
See 3 more Smart Citations